A emergência de relações condicionais entre estímulos como resultado de treino de pares de discriminações simples simultâneas - Montans, Maria Paula Soares (2006)
Stimulus and response classes are defined by a given set of shared properties. Stimulus classes are identified when different stimuli affect an organism in the same way. Processes, procedures and variables responsible for the establishment of stimulus control and stimulus classes and for the testing of such classes have been studied and today a number of authors argue that such processes and procedures may generate distinct types of stimulus classes such as functional stimulus classes and equivalent stimulus classes. Matching to sample is nowadays the choice procedure to establish conditional discriminations and classes of equivalent stimuli. Nevertheless, other procedures for the establishment of conditional discriminations among stimuli that prove to be effective for the emergence of equivalent classes have been described. The current study tested if a procedure that established errorless (or almost errorless) simple simultaneous discriminations based on discriminations already established, without any reversals, could establish conditional discriminations and equivalence classes formed by a SD series and a SΔ series of stimuli. Six children aged between 6 and 7 participated in the study. They worked in a computer equipped with a programme that controlled all the experiment conditions and also recorded the necessary data. Six experimental conditions, were successively presented: (1) simultaneous discrimination training of 3 stimuli pairs named A, B, C, (2) discriminative training of all stimuli pairs with 100% and 50% of trials reinforced, (3) conditional discrimination training, (4) test of emergent stimuli relations, (5) training and test of stimuli class formation, (6) grouping card stimuli. Results have shown that each participant has achieved criterion on the simple discrimination training of stimuli pairs A, B and C without errors or almost without errors or reversals and that the procedure allowed the establishment not only of the simple discriminations among the 3 pairs of stimuli, but also aloowed for the emergence of conditional relations among the S+ and S- stimuli series, for three participants